Influence of Principals’ Reward System on Academic Performance in Kisii County, Kenya - Ololo, Thomas Odongo; Onditi, Mary Anyango; Mwebi, Benard (International Journal of Research and Innovation in Social Science (IJRISS), 2024)
This study investigated the influence of Principals’ reward system on learners’ academic performance in Kenya Certificate of Secondary Education in Kisii County. Mixed method research design of explanatory sequential type was applied in the study. From a target population of 4,691 subjects, a sample of 366 participants derived proportionately through stratified random sampling technique which included 114 H.O. Ds and 252 teachers was sampled. Census sampling was applied to select the two national schools and one special school while the 82 other schools were sampled through proportionate stratified random sampling technique. The 85 Principals of the selected schools were purposefully sampled. The total sample for the study was 451 participants. Questionnaires and interview guides were used to collect data. Validity of the research instruments was ensured through expert evaluation while reliability was estimated by use of Cronbach’s alpha coefficient formula. Quantitative data were analysed using Statistical Package of Social Sciences (SPSS) Version 29 while qualitative data were analysed thematically. The study found out a weak positive insignificant influence between reward system of teachers and learners (r=.021, p≤.05; 2 tailed) and academic performance. This was supported by Principals’ interviews which indicated that lack of financial support make hard to reward teachers and learners and unclear promotion policy by the Teachers’ Service Commission demoralizes teachers. The findings of this study would be a base for corrective measures against low academic performance in the study locale. The study recommended that further research should be done on influence of principals’ leadership skills development on academic performance in K.C.S.E.
Keywords: Reward system; Mixed Method; Explanatory Sequential; Principals; Secondary Education